Humor, Happiness and Work Relationship among Faculty Members in Islamic Higher Education of Indonesia - Fahmi Gunawan; Alimin Alimin (Institut Agama Islam Negeri (IAIN) Kendari, 2018)
Humor is important among educators to refresh their mind from busy work, strengthen friendship and interpersonal relationship, create happiness, and to improve working performance and cooperation of both personal and professional matters. This study aims to examine the humor in the perspective of linguistics and psychology, especially the semantic aspect among colleagues of lecturers in Islamic universities of Indonesia. A qualitative-descriptive method was employed to analyze data which were collected through participants’ observation and in-depth interview. The results indicate that to create humor from a linguistic perspective, lecturers used polysemy and homonym aspects as part of the language game. Polysemy is only a word while homonym is a word, abbreviation, and acronym. The words that indicate polysemy is margacinta, hawa, and kopi, while the words that indicate homonyms in the form of words maroko, farj, and tabrakan. On the other hand, the abbreviation homonymy is found in the phrases of peraturan pemerintah and pembimbing akademik and the acronyms are found in words akper, jatol, jaka, marisa and jelita. This language game then creates a joyful atmosphere among lecturers which ultimately affects their interpersonal relationships. The proximity of interpersonal relations also has implications for better employment relations and increased productivity to do works assigned to them. Finally, this research confirms that language games such as polysemy and homonymy can also be used to create humor aimed not only to refresh mind but also to create happiness and improve work performance to increase productivity in universities.Keywords: Humor, happiness, relationship, lecturer, Islamic Higher Education.